Case series of aortic arch disease treated with branched stent‐grafts. Issue 4 (28th February 2018) - Clough, R. E.; Spear, R.; Van Calster, K.; Hertault, A.; Azzaoui, R.; Sobocinski, J.; Fabre, D.; Haulon, S.
Abstract : Background: Surgical repair of aortic arch pathology is complex and associated with significant morbidity and mortality. Alternative approaches have been developed to reduce these risks, including the use of thoracic stent‐grafts with fenestrations or in combination with bypass procedures to maintain supra‐aortic trunk blood flow. Branched stent‐grafts are a novel approach to treat aortic arch pathology. Methods: Consecutive patients with aortic arch disease presenting to a single university hospital vascular centre were considered for branched stent‐graft repair (October 2010 to January 2017). Patients were assessed in a multidisciplinary setting including a cardiologist, cardiac surgeon and vascular surgeon. All patients were considered prohibitively high risk for standard open surgical repair. The study used reporting standards for endovascular aortic repair and PROCESS (Preferred Reporting of Case Series in Surgery) guidelines. Results: Some 30 patients (25 men) underwent attempted branch stent‐graft repair. Mean age was 68 (range 37–84) years. Eighteen patients had chronic aortic dissection, 11 patients had an aneurysm and one had a penetrating ulcer. Fourteen patients had disease in aortic arch zone 0, six in zone 1 and ten in zone 2. Twenty‐five patients had undergone previous aortic surgery and 24 required surgical revascularization of the left subclavian artery. Technical success was achieved in 27 of 30 patients. Four patients had an endoleak (type Ia, 1; type II, 3). The in‐hospital mortality rate was three of 30. Mean length of follow‐up was 12·0 (range 1·0–67·8) months, during which time 12 patients required an aortic‐related reintervention. Conclusion: Repair of aortic arch pathology using branched stent‐grafting appears feasible. Before widespread adoption of this technology, further studies are required to standardize the technique and identify which patients are most likely to benefit. Abstract : Encouraging results in expert hands